Farmacovigilância no Brasil: descrição e fatores associados à subnotificação e aos desfechos graves dos eventos adversos a medicamentos - Melo, José Romério Rabêlo (2022)
Adverse Drug Events (ADE) are a public health problem, with high rates of morbidity and mortality and impacts on health systems costs. Voluntary reporting in passive surveillance systems is the most used strategy to identify ADE. However, underreporting represents a challenge in preventing these events. This thesis describes the profile of notification and participants in the National Pharmacovigilance System (SINAF) and analyzes the factors associated with underreporting, severity and deaths in patients with ADE. To achieve the proposed objectives, data from the Notivisa, VigiMed, hospital admission System (SIH) and Mortality Information System (SIM) systems were used - and data from the Knowledge, Attitudes, and Practices survey (KAP) in Pharmacovigilance with the Brazilian health professionals. A systematic review of the literature of articles with ICD-10 ADE triggering codes was carried out, in which the most used were identified and a list of the most concordant among the articles reviewed was created. The ICDs on this list were identified in the SIH and SIM data. Statistical analyzes included: i) use of relative frequencies and estimation of 95%CI; chi-square, Fisher's exact, t and Mann-Whitney tests; iii) multivariable methods using non-conditional multivariable logistic regression, estimating the raw and adjusted odd ratios (OR). Analyzes were performed using software Stata version 10, and the open-source software R. The results of this thesis are presented in six articles. In summary, the results indicated that health professionals in general have a low level of KAP (56.6%), while the proportion of professionals who underreported ADE was 67.5%. The ADE notification rate in Notivisa was 40.8 per million inhabitants. Based on the SIH and SIM records, the drugs that most caused ADE, proportionally, were those that act on the nervous system, antineoplastic, and immunomodulators. The proportion of patients with ADE during hospitalization was 0.53%, and the risk of death among them during hospitalization is 1.8%. With respect to ADE reports among patients with Covid-19, chloroquine (OR = 5.4) and hydroxychloroquine (OR = 2.1) were the only drugs associated with severe ADR. The results contribute to the debate to overcome the main limitations of SINAF, such as underreporting and low rates of KAP from health professionals; and assists in the search for coping strategies with, such as using active methods of ADE, focus on continuing education in pharmacovigilance for health professionals and promoting the culture of ADE notification in Brazil.